SINTESIS DAN UJI TOKSISITAS SENYAWA ANALOG KURKUMIN 3,5-BIS((E)-METOKSI BENZILIDEN)-1-(FENILSULFONIL)-PIPERIDIN-4-ON - Rahmawati, E. N.; Teruna, H. Y.; Zhamri, A. (Sistem Informasi, 2018)
A study has been conducted to synthesize analog of curcumin with base catalyzed condensation of 4-piperidone hydrochloride with substituted benzaldehyde under reflux led the formation of mono-carbonyl curcumin. The synthesized curcumin were further reacted with benzosulphonyl chloride by nucleophilic substitution of âNH group to afford 3,5-bis((E)-2-metoksi benziliden)-1-(fenilsulfonil)piperidin-4-on (EN-BS) compounds with excellent yield, 94%. Structure of the synthesized compounds were confirmed by UV, IR, MS and NMR spectra analysis. All the synthesized compounds were screened for their toxicity activity using BSLT method. The result showed that compounds are toxic whereas the LC50 is below 200 ppm.